Marinas as habitats for nearshore fish assemblages: comparative analysis of underwater visual census, baited cameras and fish traps - Bosch, Nestor E. (2017)
Understanding the ecological role that artificial structures might play on nearshore fish assemblages requires the collection of accurate and reliable data through efficient sampling techniques. In this work, differences in the composition and structure of fish assemblages between the inner and outer sides of three marinas located in the temperate northern-eastern Atlantic Ocean were tested using three complementary sampling techniques: underwater visual censuses (UVC), baited cameras (BCs) and fish traps (FTs). UVCs and BCs recorded a comparable number and relative abundance of species, which in turn were much greater than those recorded by FTs. This finding supports the use of UVCs and BCs over FTs for broad ecologically studies, especially when dealing with structurally complex habitats such as artificial structures. We found differences in fish assemblage structure between the inner and outer sides of marinas, independently of the sampling method. Four small-sized species (Similiparma lurida, Thalassoma pavo, Sarpa salpa and Symphodus roissali) associated with structurally complex vegetated habitats dominated, in terms of abundance, the outer sides of marinas; Diplodus vulgaris, Diplodus sargus and Gobius niger, species with high ecological plasticity in habitat requirements, dominated the inner sides of marinas. The information provided in this study is of great interest for developing sound monitoring programmes to ascertain the effects of artificial structures on fish communities.